2016
DOI: 10.24867/jged-2016-1-005
|View full text |Cite
|
Sign up to set email alerts
|

Eye-tracking analysis of face observing and face recognition

Abstract: (universities, research organizations, companies, associations, etc.) (conferences, symposia, and meetings). KEy WoRDSEye tracking, face recognition, fixation duration, face elements, area of interest, heat maps eye-tracking analysis of face observing and face recognition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
5
0
3
Order By: Relevance
“…As an example, Figure 3 is a graphical representation of the average visual behavior observed when a face (i.e., model 4) was explored. We can observe the triangular geometric pattern that runs from one eye to the next and then down to the mouth and then back to the first eye ( Iskra and Gabrijelcic, 2016 ), with extents of preference in the eyes–mouth continuum ( Rogers et al, 2018 ) when tearless faces were judged and with brief fixation times and spreading points over the face. As the figure shows, the presence of tears alters the visual inspection pattern, breaking the triangle of fixations concentrating them inside the AOI, as if tears were powerful visual attention magnets.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, Figure 3 is a graphical representation of the average visual behavior observed when a face (i.e., model 4) was explored. We can observe the triangular geometric pattern that runs from one eye to the next and then down to the mouth and then back to the first eye ( Iskra and Gabrijelcic, 2016 ), with extents of preference in the eyes–mouth continuum ( Rogers et al, 2018 ) when tearless faces were judged and with brief fixation times and spreading points over the face. As the figure shows, the presence of tears alters the visual inspection pattern, breaking the triangle of fixations concentrating them inside the AOI, as if tears were powerful visual attention magnets.…”
Section: Resultsmentioning
confidence: 99%
“…Quinn and Tanaka (2009) have shown that also infants 3- to 7-month-olds tend to visually explore more the higher part of the face, and to fixate for longer time a version of the face with enlarged eyes. The preference for the eye region when looking at faces was also demonstrated by Iskra and Gabrijelčič Tomc (2016) by asking adults to watch faces of different age. Considering a 4 s presentation, the eyes were observed for the 52.7% of the time, the mouth the 15.5% and the nose the 10.8%.…”
Section: Discussionmentioning
confidence: 98%
“…Irregular polygons around the neck (artifact from the computer generation of the masks) and the cranial stockinette that was present on the original child with craniosynostosis (used to acquire 3D photography if the child had significant hair) were pointed out as unrelated prior to the presentation. Each image was shown for 4 seconds, a previously cited duration in eye tracking literature for evaluating faces (Iskra, 2016; Dindaroglu et al, 2017). While the image was shown, the investigator wrote the participant’s stated answer on the survey sheet.…”
Section: Methodsmentioning
confidence: 99%